Work-related ageism: management challenges - Reis, Maria Manuela Jacob Cebola Luzia (2024)
The present investigation aims to identify management challenges regarding work-related ageism, especially concerning a hiring process or the recognition and award of professional merit, and to propose strategic measures to prevent and manage ageism that are useful for organizations and people management. A SLR was carried out to obtain a comprehensive and accurate picture of the empirical research on worker-related ageism. Then we conducted a study on the relationships between ageism and decent work and the workplace relationships intergenerational climates in workplaces. Simultaneously, we conducted the necessary procedures to develop and validate the Nordic Age Discrimination Scale (NADS) and the Workplace Intergenerational Climate Scale (WICS). Two other gaps we sought to respond to, contributing to the field of research and management, were the scarcity of experimental studies and studies on the public recognition of professional merit. To this end, we conducted an experimental design study to evaluate how peers discriminate by age against candidates for a job and a professional merit award. The complementarity of this study contributes significantly to the area of research and management and provides a valuable resource for future research in this area. It highlights how the negative and positive correlations between ageism, decent work, and intergenerational relationships at work are interrelated and how they influence each other. The study proposes strategies designed to help minimize ageism in selecting candidates from CVs, maximizing the added value that each individual can bring to the organization and the economy by avoiding denying opportunities to skilled and talented individuals based solely on age. Furthermore, these strategies help minimize adverse mental health outcomes associated with ageism in the workplace, which also benefits companies and organizations due to the lower rate of absenteeism among their workers due to mental illness associated with ageism; - Resumo: Idadismo relacionado com o trabalho: Desafios de gestão A presente investigação tem como objetivo identificar os desafios de gestão relativos à relação idadismo e trabalho, especialmente no que diz respeito ao processo de contratação ou ao reconhecimento e atribuição do mérito profissional, e propor medidas estratégicas de prevenção e gestão do idadismo que sejam úteis para as organizações e para a gestão de pessoas. Foi realizada uma RSL para obter uma imagem abrangente e precisa da investigação empírica sobre o idadismo relacionado com os trabalhadores. Realizámos um estudo sobre as relações entre o idadismo e o trabalho digno, e as relações intergeracionais nos locais de trabalho e, simultaneamente, efetuámos os procedimentos necessários para desenvolver e validar dois instrumentos de medição do idadismo. Empreendemos um estudo de desenho experimental para avaliar como os pares discriminam por idade os candidatos a um emprego e a um premio de mérito profissional. A complementaridade deste estudo destaca como as correlações negativas e positivas entre o idadismo, o trabalho digno e as relações intergeracionais no trabalho estão inter-relacionadas e como se influenciam mutuamente. A abordagem única de desenho experimental do estudo permite uma melhor compreensão do idadismo implícito e explícito na força de trabalho. O estudo propõe estratégias concebidas para ajudar a minimizar o idadismo na seleção de candidatos a partir de currículos, maximizando o valor acrescentado que cada indivíduo pode trazer para a organização e para a economia, evitando negar oportunidades a indivíduos qualificados e talentosos com base apenas na idade. Além disso, estas estratégias podem ajudar a minimizar os resultados adversos para a saúde mental associados ao idadismo no local de trabalho, o que beneficia também as empresas e organizações pelo menor índice de absentismo dos seus trabalhadores por doença mental a ele associados.